Adverse effects of Herceptin treatment in women with breast cancer in Hillah (Iraq) - Al Sa’ady, Amal Talib; Alisawi, Lina; Hasan Al-Shareefy, Dhafar Mohamed; H. Kadhum, Nadia; Mutar, Hamid Khalaf; Khlaif, Ghadeer Talib (Pharmakeftiki, 2025)
Herceptin (trastuzumab) is a targeted anticancer therapy that has significantly improved outcomes in the treatment of human epidermal growth factor receptor 2 (HER2)-positive breast cancer since its introduction in 1998. This study has employed a retrospective cross-sectional design using a paper-based questionnaire administered to women with breast cancer and receiving Herceptin at the Oncology Center of the Imam Sadiq Teaching Hospital and at the Marjan Medical City Hospital in Hillah, Iraq. The study period spanned from 1 November 2022 to 31 March 2023. A total of 50 Iraqi women aged 21 to 71 years participated in the study. The most common age groups were 41–50 and 51–60 years. Of the participants, 49 (98%) had undergone breast surgery. Seventeen distinct adverse effects associated with Herceptin use were reported, with all patients (100%) experiencing at least one. The most frequently reported effects included fatigue, exhaustion, and loss of energy, bone and muscle pain, headache, anorexia, gastrointestinal pain (cramping), sleep disturbances, visual disturbances, as well as bloating and increased abdominal size. These were followed by drowsiness, prolonged sleep, cardiac issues, anaemia, itching and skin allergies, as well as immunodeficiency. Less common adverse effects included hypertension, hyperglycaemia, kidney problems, and hypercholesterolaemia. Eighteen women (36%) experienced infusion-related reactions, including allergic-like responses and anaphylaxis. Other reported infusion-related reactions included vomiting, severe chills, muscle tremors, high fever, loss of motor control, coughing and choking, shortness of breath, jaw tremors, and temporary loss of speech.